2004
DOI: 10.1016/j.physleta.2004.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Light driven structuring of glasses

Abstract: Theoretical and experimental evidence of light driven structuring of glasses is presented. We show that light overcomes Coulomb repulsion and effective electron-electron interaction in glasses under strong light pumping becomes attractive. As the result homogenious distribution of trapped electrons gets unstable and macroscopic electron bunches are grown. At different conditions ordered structures with period 2µm ± 0.2µm determined by internal properties of the material are formed These structures were observe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…figure 9 (respectively, in the horizontal and the vertical direction). In all cases the period of the self-organized structure, figures 5-9, was 2 AE 0:2 mm and coincided with periods found in our other experiments [10,11]. The period is a characteristic of the matter but not the light and the fact confirms the self-organized nature of the ordering discussed.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…figure 9 (respectively, in the horizontal and the vertical direction). In all cases the period of the self-organized structure, figures 5-9, was 2 AE 0:2 mm and coincided with periods found in our other experiments [10,11]. The period is a characteristic of the matter but not the light and the fact confirms the self-organized nature of the ordering discussed.…”
Section: Methodssupporting
confidence: 89%
“…As a result static polarization directed against the external electric field is established. This polarization amplifies the initial field and the process is stopped at the value of the field 10 5 to 10 7 V cm À1 (for details see [10,11]). At the achieved field of saturation, lightinduced transitions are in the dynamical equilibrium with contraflow due to the ordinary electron mobility.…”
Section: Electron Bunching Under Light Pumpingmentioning
confidence: 99%
“…The third electron is transported to the bielectron and so on. We observed this light driven bunching [6,7] under laser pumping in ablation due to Franz-Keldysh effect [12,13]. We found that for different light parameters-power, beam size, coherent length-ordered structure of electron-hole bunches with the same period is formed.…”
Section: Article In Pressmentioning
confidence: 93%
“…In the latter case light amplitude has been modulated in time and space, which was crucial for the organization to occur. Our investigations [5][6][7][8] have shown that steady light flow through a system can provide ordering either. This light is a driving force which bunches the electrons together.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to the poor thermal properties of most glass the fabrication of finely machined features such as micro-grooves and micro-holes has been a challenging task. Antonyuk et al (2008) applied an ArF laser beam to effectively act as a drill to produce a micron radius channel up to 1 cm long in fused quartz (the diameter of the light spot was a few millimeters). Nikumb et al (2005) utilized the short pulse solid-state lasers with pulse duration in the nano-to femto-second range to process different types of glass materials.…”
Section: Introductionmentioning
confidence: 99%